Automation - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2023)
Patterns could be expressed in numbers [1]. Numbers can be used to communicate in everyday life [2]. At the smallest scale, information as stored as 0 and 1[2]. The purpose of this paper is to propose automation through a simple ordering process. It is about automating our tasks by using the information above that everything is stored as 0 and 1 at the smallest scale. This information could be used to automate our tasks in information and software systems.